2016
DOI: 10.1177/0885328216650125
|View full text |Cite
|
Sign up to set email alerts
|

Triethyl orthoformate covalently cross-linked chitosan-(poly vinyl) alcohol based biodegradable scaffolds with heparin-binding ability for promoting neovascularisation

Abstract: ReuseUnless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or other rights-holder may allow further reproduction and re-use of this version -refer to the White Rose Research Online record for this item. Where records identify the publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…Chitosan was present on the top surface and the corresponding spectra showed a band for alkyl (CH 2 , CH 3 ) bending at 1375-1415 cm − 1 , a small hump between 1586 and 1650 cm − 1 corresponding to the CO stretching from Amide I, and, the peaks of CH 2 , CH 3 stretch near 2850-2915 cm − 1 24,41 . These spectra also showed a band between 1025-1060 cm − 1 assigned to C-O-C stretching and a broad peak at 3555 cm − 1 , which may be attributed to a combination of OH and NH, stretching vibrations 24,41 .…”
Section: Ftir Characterizationmentioning
confidence: 97%
See 1 more Smart Citation
“…Chitosan was present on the top surface and the corresponding spectra showed a band for alkyl (CH 2 , CH 3 ) bending at 1375-1415 cm − 1 , a small hump between 1586 and 1650 cm − 1 corresponding to the CO stretching from Amide I, and, the peaks of CH 2 , CH 3 stretch near 2850-2915 cm − 1 24,41 . These spectra also showed a band between 1025-1060 cm − 1 assigned to C-O-C stretching and a broad peak at 3555 cm − 1 , which may be attributed to a combination of OH and NH, stretching vibrations 24,41 .…”
Section: Ftir Characterizationmentioning
confidence: 97%
“…Regardless of the vast information available regarding the use of heparin to bind growth factors to scaffolds, not many studies regarding the angiogenic in uence of heparin itself on the bone healing process have been reported. Recently, our research group reported on the use of heparin loaded hydrogels as an angiogenic promoter for wound healing treatments [22][23][24] . On the other hand, Gümüşderelioğlu & Aday (2011) reported the osteogenic activity of heparinised chitosan scaffolds promoting in vitro proliferation and differentiation of pre-osteoblasts cells 25 .…”
Section: Introductionmentioning
confidence: 99%
“…It also regulates their stability and biological activity as well as long-term stimulation of endothelial cells [22 24]. Our group has explored the approach of using heparin bound to biomaterials to deliver VEGF using a layerby-layer method for coating scaffolds with heparin and then binding VEGF [25] and we have also reported on chitosan-based hydrogels for binding heparin [26,27]. However, binding VEGF with heparin is a long process and requires multistep actions to introduce VEGF with the TE scaffolds.…”
Section: Introductionmentioning
confidence: 99%
“…Recently in our group, heparin was exploited to induce angiogenesis investigated via CAM assay to evaluate the potential attachment of physiologically available angiogenic growth factors to pro-angiogenic receptors by using heparin bonded chemically crosslinked chitosan poly-vinyl alcohol (PVA) hydrogels. Triethyl orthoformate (TEOF) crosslinked and heparin bonded hydrogels led to more blood vessel generation as compared to heparin-free control samples [62]. In addition, direct mixing of heparin in chitosan-PVA-PCL hydrogels in the absence of any growth factors was investigated for angiogenesis on chick embryo's CAM tissues for wound healing application.…”
Section: Introductionmentioning
confidence: 99%